On Small Primary Modules - Abdul-AlKalik, Adwia Jassim (Iraqi Journal of Science, 2021)
Let be a commutative ring with an identity and be a unitary -module. We say that a non-zero submodule of is primary if for each with en either or and an -module is a small primary if = for each proper submodule small in. We provided and demonstrated some of the characterizations and features of these types of submodules (modules).